Lysine biofortification of crops to promote sustained human health in the 21st century. (1st November 2021) - Yang, Qingqing; Zhao, Dongsheng; Zhang, Chuangquan; Sreenivasulu, Nese; Sun, Samuel Sai-Ming; Liu, Qiaoquan
Abstract: Crop biofortification is pivotal in preventing malnutrition, with lysine considered the main limiting essential amino acid (EAA) required to maintain human health. Lysine deficiency is predominant in developing countries where cereal crops are the staple food, highlighting the need for efforts aimed at enriching the staple diet through lysine biofortification. Successful modification of aspartate kinase (AK) and dihydrodipicolinate synthase (DHDPS) feedback inhibition has been used to enrich lysine in transgenic rice plants without yield penalty, while increases in the lysine content of quality protein maize have been achieved via marker-assisted selection. Here, we reviewed the lysine metabolic pathway and proposed the use of metabolic engineering targets as the preferred option for fortification of lysine in crops. Use of gene editing technologies to translate the findings and engineer lysine catabolism is thus a pioneering step forward. Abstract : We review strategies for lysine biofortification of staple crops by modulating lysine metabolism and seed storage protein profiles.